South Station Hoard: Imagining, Creating and Empowering Violent Remains - Bradbury, Carlee A (punctum books, 2014)
This collaborative arts research project compares the landmark discovery of the Staffordshire Hoard, the largest hoard of Anglo-Saxon gold and silver metalwork discovered in 2009, with an imagined hoard from present day pre-adolescent girls. The collaborators constructed a subterranean installation, generated speculative historical documents, collected and embellished social networking "artifacts," and photographed the entire process. In addition to dealing with the notion of a medieval hoard as a signifier of a medieval warrior as both hero and anti-hero, this artbook, or work of futurist archaeology, addresses contemporary issues relating to gender, youth culture, bullying, adolescent development, iconicity, status symbols, and additional contemporary tween issues.